Salinity-driven nitrogen removal and its quantitative molecular mechanisms in artificial tidal wetlands - Zhang, Manping; Wang, Zi-Jing; Huang, Jung-Chen; Sun, Shanshan; Cui, Xijun; Zhou, Weili; He, Shengbing (Water research (Oxford), 2021)
•Salinity significantly affected nitrogen removal in artificial tidal wetlands.•High and stable NH4+ removal efficiency (about 85%) was achieved for all salinities.•NO3− (6.34-89.19%) and TN (22.54-87.48%) removal rates varied with salinity levels.•Simultaneous nitrification, denitrification, anammox and DNRA contributed to N loss. • A more efficient system was developed for saline wastewater treatment. The present study investigated the performance in nitrogen removal and associated nitrogen transformation processes in seven mesocosms fed with saline water (0‰ to 30‰) to simulate tidal flow constructed wetlands (TF CWs). The highly effective and steady removal of NH4+-N (84.74% averagely) was obtained at various salinities, while the rates varied from 6.34% to 89.19% and 22.54% to 87.48% for NO3−-N and total nitrogen (TN), respectively. Overall, nitrogen removal efficiencies were greater at lower salinities. Molecular biological analyses verified the co-occurrence of dissimilatory nitrate reduction to ammonium (DNRA), denitrification, anaerobic ammonium oxidation (anammox) and nitrification in the mesocosms, reportedly contributing to nitrogen removal in TF CWs. The absolute copy numbers of nitrogen functional genes and total bacterial 16S rRNA were 2.54 × 103-7.35 × 107 and 3.21 × 107-7.82 × 109 copies g−1 dg (dry gravel), respectively, with the dominant phyla, i.e., Chloroflexi, Proteobacteria, Actinobacteriota, Cyanobacteria, and Firmicutes, accounting for over 80% of the sequences. The relative abundances of the genera related to nitrification and dissimilatory nitrate reduction processes, i.e., denitrification, anammox and DNRA, varied from 0.16% to 0.89% and from 3.66% to 11.59%, respectively, while quantitative relationships confirmed NH4+-N transformation rate was jointly controlled by amoA, hzsB, nxrA and nrfA, and NO3−-N removal rate by nirS, nosZ, narG, qnorB and nxrA. These findings may shed light on quantitative molecular mechanisms for nitrogen removal in TF CWs for the saline water treatment, providing a sustainable solution to nitrogen pollution problem in the estuary ecosystem. [Display omitted]